The spatial distribution pattern of coffee shops in Kuta Alam District, Banda Aceh - Yusuf, Myna Agustina; Nurnazirah, Nurnazirah; Arafah, Yunita (Geuthèë Institute, Aceh, 2024)
The Aceh Province, recognized as one of the world's finest coffee producers, is also known as the